Digital Opportunities for the Technical Implements in Livestock Production - Kovács, Imre (Animal welfare, Ethology and Housing Systems (AWETH), 2017)
We stand on the brink of a new revolution that will fundamentally change the way we live and work. The complexity and the transformation of this technological revolution will be unlike anything humankind has experienced before. The term “Industry 4.0 stands for the fourth industrial revolution. It is characterized by a fusion of technologies that is blurring the lines between the physical, digital and biological spheres. Industry 4.0 introduces what has been called the “Smart factory, in which cyber-physical systems monitor the physical processes of the factory and make decentralized decisions.These deep changes also influence the way companies and farmers produce their food and radically changes precision agriculture or smart farming. Agriculture differs from industry in several aspects but smart technologies can also be used in agricultural production. Precision Livestock Farming (PLF) systems offer solutions to all of livestock technology. These systems there are for examples precision feeding systems, precision milking robot and stable and farm management systems.
Keywords: industry 4.0; digital implements; smart farming; robotics; Agriculture 4.0.